Low dose aspirin and cognitive function in middle aged to elderly adults: randomised controlled trial. (1st September 2008) - Price, Jackie F; Stewart, Marlene C; Deary, Ian J; Murray, Gordon D; Sandercock, Peter; Butcher, Isabella; Fowkes, F Gerald R
Abstract : Objective To determine the effects of low dose aspirin on cognitive function in middle aged to elderly men and women at moderately increased cardiovascular risk. Design Randomised double blind placebo controlled trial. Setting Central Scotland. Participants 3350 men and women aged over 50 participating in the aspirin for asymptomatic atherosclerosis trial. Intervention Low dose aspirin (100 mg daily) or placebo for five years. Main outcome measures Tests of memory, executive function, non-verbal reasoning, mental flexibility, and information processing five years after randomisation, with scores used to create a summary cognitive score (general factor). Results At baseline, mean vocabulary scores (an indicator of previous cognitive ability) were similar in the aspirin (30.9, SD 4.7) and placebo (31.1, SD 4.7) groups. In the primary intention to treat analysis, there was no significant difference at follow-up between the groups in the proportion achieving over the median general factor cognitive score (32.7% and 34.8% respectively, odds ratio 0.91, 95% confidence interval 0.79 to 1.05, P=0.20) or in mean scores on the individual cognitive tests. There were also no significant differences in change in cognitive ability over the five years in a subset of 504 who underwent detailed cognitive testing at baseline. Conclusion Low dose aspirin does not affect cognitive function in middle aged to elderly people at increased cardiovascular risk. Trial registration ISRCTN 66587262.